Contextualization of Prophet Ibrahim's Interpersonal Communication in the Present Era - Moh. Mashadi; Abad Badruzaman; Ahmad Zainal Abidin; Abdunrorma Sama Alee (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
Interpersonal communication is a form of interconnection and interaction (reciprocal actions) to achieve desired goals. The Qur'an's attention to good communication is found, among other places, in the story of Prophet Ibrahim. This study, based on Julia T. Wood's theory, examines Prophet Ibrahim's interpersonal communication in the Qur'an, focusing on two issues: how does Prophet Ibrahim's linear, interactional, and transactional interpersonal communication appear in the Qur'an? and how can Prophet Ibrahim's interpersonal communication be contextualized in the present era? This study uses a library research approach with the Qur'an and Tafsir as the primary sources, supported by secondary sources such as books, journals, and other relevant documents. The results of the study show that Prophet Ibrahim's interpersonal communication according to Julia T. Wood's theory consists of linear, interactional, and transactional models. The linear model consists of communication with children, communities, and fathers and communities; the interactional model consists of communication with guests, fathers, and children; and the transactional model consists of communication with fathers and communities, kings, and guests. The contextualization of the linear model consists of character building for children, the reasons why Allah must be worshipped, and the declaration of freedom from worshipping anything other than Allah. The contextualization of the interactional model involves arguments about salvation, arguments to show the mistakes of the interlocutor, commands to be persuasive, and hissiyah enjoyment. The contextualization of the transactional model involves the search for the essence of God, evidence of God's omnipotence, the concept of ikram al-dayf, and the importance of arguments based on nash.